O-arm-guided percutaneous microwave ablation and cementoplasty for the treatment of pelvic acetabulum bone metastasis - Zuo, Dongqing; Sun, Mengxiong; Mu, Haoran; Shen, Jiakang; Wang, Chongren; Sun, Wei; Cai, Zhengdong (Frontiers in Surgery, 2022)
Objective: To evaluate the indications, safety and efficacy of microwave ablation combined with cementoplasty under O-arm navigation for the treatment of painful pelvic bone metastasis. Methods: We retrospectively collected data from 25 patients with acetabulum bone metastasis who underwent microwave ablation combined with cementoplasty. All patients underwent percutaneous microwave ablation combined with cementoplasty under o-arm navigation. The postoperative follow-up included evaluations of pain, quality of life, function, incidence of bone cement leakage and the presence of perioperative complications. Pain and quality of life were evaluated by the visual analog scale (VAS), the QLQ-BM22 quality of life questionnaire for patients with bone metastases, respectively. and the functional score were according to the MSTS93 scoring system of the Bone and Soft Tissue Oncology Society. Results: There were 10 males and 15 females with an average age of 52.5 ± 6.5 years, all 25 patients received percutaneous procedures, and no technical failure occurred. Major complications, including pulmonary embolism, vascular or nervous injury, hip joint cement leakage, and infection, were not observed in the current study. Pain regression was achieved in 24 of 25 patients. The mean VAS scores significantly decreased to 3.4±1.0, 2.5±1.2 and 1.2±0.6 points at 1 week, 1 month and 3 months after the procedure, respectively, compared with 7.0 points before the procedure (P < 0.05). The mean QLQ-BM22 score significantly decreased to 36.2±4.9, 30±5.6 and 25.4±2.3 points at 1 week, 1 month and 3 months after the procedure, respectively, compared with 55.8 points before the procedure (P < 0.05). The preoperative MSTS score of 25 patients was 18.5±5.3 points, and MSTS score was 20.0±3.0, 21.4±4.9 and 22.8±2.3 at 1 week, 1 month and 3 months after the procedure, respectively (P< 0.05).The average bone cement injection volume was 8.8 ± 4.6 ml. Conclusion: The use of O-arm-guided percutaneous microwave ablation combined with cementoplasty for the treatment of pelvic metastases could quickly and significantly alleviate local pain, prevent pathological fracture and improve the quality of life of patients with reduced complications.